Analysis of Microplastic in Ice Cubes Around Mulawarman University Gunung Kelua sub-District: Analisis Kandungan Mikroplastik pada Es Batu di sekitar Universitas Mulawarman Kelurahan Gunung Kelua - Fajrina, Dinda Nur; Boleng, Didimus Tanah; Tinekke Lumowa, Sonnja Verra (Universitas Muhammadiyah Sidoarjo, 2023)
Analysis of Microplastic in Ice Cubes Around Mulawarman University Gunung Kelua sub-district, thesis for Biology Education Study Program, Faculty of Teacher Training and Education, Mulawarman University, Research Under the Guidance of Prof. Dr. Didimus Tanah Boleng, M.Kes and Dr. Sonja Verra Tinneke Lumowa, M. Kes as supervisor I and II. This study aims to determine the microplastic in ice cubes and to determine the shape, color, and abundance of microplastics in ice cubes around Mulawarman University, Gunung Kelua sub-district. The type of research used is descriptive quantitative. Sampling with purposive sampling technique. The data analysis technique is quantitative descriptive by identifying and classifying it based on the shape, color, and abundance of microplastics in the ice cubes. The results of the research on the analysis of the microplastic in ice cubes around Mulawarman University Gunung Kelua sub-district, showed that all samples of the tested ice cubes contained positive microplastics. Microplastics in ice cubes with AMIU 1 as raw material have an abundance of 10 particles/L in the form of fibers, fragments and films with black, red, blue and transparent colors. Microplastics in ice cubes with AMIU 2 raw materials have an abundance of 9 particles/L in the form of fibers and fragments with black and red colors. Microplastics in ice cubes with PDAM 1 as raw material have an abundance of 22 particles/L in the form of fibers, fragments, and films with black, red, blue, purple, transparent, and yellow colors. Microplastics in ice cubes made from PDAM 2 have an abundance of 17 particles in the form of fibers and fragments with black, red and blue colors. Microplastics in crystal ice cubes have an abundance of 29 particles/L in the form of fibers, fragments and films with black, red, purple and transparent colors.